GRK5-Knockout Mice Generated by TALEN-Mediated Gene Targeting. Issue 4 (1st October 2016) - Nanjidsuren, Tsevelmaa; Park, Chae-Won; Sim, Bo-Woong; Kim, Sun-Uk; Chang, Kyu-Tae; Kang, Myung-Hwa; Min, Kwan-Sik
ABSTRACT: Transcription activator-like effector nucleases (TALENs) are a new type of engineered nuclease that is very effective for directed gene disruption in any genome sequence. We investigated the generation of mice with genetic knockout (KO) of the G protein-coupled receptor kinase (GRK) 5 gene by microinjection of TALEN mRNA. TALEN vectors were designed to target exons 1, 3, and 5 of the mouse GRK5 gene. Flow cytometry showed that the activity of the TALEN mRNAs targeted to exons 1, 3, and 5 was 8.7%, 9.7%, and 12.7%, respectively. The TALEN mRNA for exon 5 was injected into the cytoplasm of 180 one-cell embryos. Of the 53 newborns, three (5.6%) were mutant founders (F0 ) with mutations. Two clones from F0 28 showed a 45-bp deletion and F0 39 showed the same biallelic non-frame-shifting 3-bp deletions. Three clones from F0 41 were shown to possess a combination of frame-shifting 2-bp deletions. All of the mutations were transmitted through the germline but not to all progenies (37.5%, 37.5%, and 57.1% for the F0 28, F0 39, and F0 41 lines, respectively). The homozygote GRK5-KO mice for 28 and 41 lines created on F3 progenies and the homozygous genotype was confirmed by PCR, T7E1 assay and sequencing.